The Effect of Chamomile and Saffron Herbal Tea Consumption on Salivary pH: A Clinical Trial Study - Masoomeh Shirzaiy (Journal of Mashhad Dental School, 2023)
Introduction: Chamomile and saffron seems to significantly decrease the level of Streptococcus mutans in saliva and reduce the likelihood of caries. The present study aimed to investigate the effect of chamomile and saffron infusion consumption on the pH of saliva.Materials & Methods: In this clinical trial study, samples were collected for salivary pH from 30 healthy male dental students over 20 to 30 years. In this method, each volunteer was asked to trickle unstimulated saliva into the test tubes through their lower lip within 3 min and every 60 s (in a seated position) before consuming chamomile or saffron (10-12 AM) infusion. After 30 min the samples were recollected 1, 5, and 10 min after ingestion of 150 ml chamomile or saffron without any sweetener in separate tubes (for each volunteer, test tubes were numbered 1 to 4) and it was transferred to the laboratory to evaluate salivary pH. The amount of salivary pH was measured by a digital pH meter in the laboratory. Data were analyzed using SPSS (version 21) by T-test, ANOVA, and repeated measurements.Results: The mean salivary pH was significantly different before chamomile consumption (7.26±0.55) and after that (7.71±0.33) (P=0.0001). A significant difference was observed between the mean salivary pH before saffron consumption (7.54±0.33) and after that (7.87±0.16) (P=0.0001). The mean salivary pH was significantly higher after saffron consumption than that after chamomile consumption (P=0.02).Conclusion: Chamomile and saffron consumption significantly increase the salivary pH and saffron has a greater effect on the salivary pH than chamomile.